Analysis of Differences in Language Development Learning Tools in Indonesian and Malaysian PAUD Institutions - Ashari, Novita; Samaun, Siti Salina Binti; Nurzhafirah, Nurzhafirah; At, St. Hajar Dilla (Journal of Early Childhood Education (JECE), 2024)
Learning tools are important in supporting the successful implementation of learning activities. Each country's learning process certainly differs from other countries learning processes. Likewise with Indonesia and Malaysia. This research aims to analyze the  differences in language development learning tools, especially beginning reading, in PAUD institutions in Malaysia and Indonesia. This research uses qualitative methods with a case study type of research. Data collection techniques in this research are interview techniques and documentation. Interviews were conducted with school principals and teachers regarding the children's language development learning tools used at the two PAUD institutions. Documentation techniques are carried out as a way of obtaining data in the form of notes or verbally based on the researcher's wishes. The research results show that there are differences between the learning tools used at the two PAUD institutions in Indonesia and Malaysia in language learning. The curriculum used by the two PAUD institutions in the two countries is different, so the learning tools used are also different.